The Effect of Administration of Rosella Flower (Hibiscus Sabdariffa) Extract Gel on The Expression Of TNF-α And Caspase-3 Expression in An In Vivo Study of Wistar Strain Rats Exposed to Ultraviolet B-Lights - Purboningtyas, Dyah Nisma; Lumbantobing, Christina J.R.E.; Lubis, Yolanda Eliza Putri (PT Inovasi Pratama Internasional, 2024)
UV rays are oxidative because they can produce Reactive Oxygen Species and free radical compounds. The dangers of sun exposure can cause skin disorders such as aging at an early age (photoaging). Rosella flower petals can be used in medicine, jams, and natural food coloring because they contain flavonoids as antioxidants or free radical scavengers. The research aimed to determine the effect of administering Rosella (Hibiscus sabdariffa L.) flower extract gel on TNF-α expression and Caspase-3 expression in an in vivo study of Wistar mice exposed to UVB. This research is an experimental study. The sample for each treatment group consisted of 6 individuals, so the total research sample was 24. Data analysis used descriptive, normality, and homogeneity tests with data analysis processing using SPSS 25.0 for Windows. The study found that administration of rosella flower extract gel with a concentration of 15% effectively reduced the expression of TNF-α and Caspase-3 in mice exposed to UVB light and produced filled and dense collagen. So, it can be concluded that rosella flower extract gel can act as an antioxidant that inhibits the growth of TNF-α and Caspase-3 expression.